Meningkatkan Jumlah Siswa dan Kualitas Akademik Siswa Melalui Peran Kepemimpinan Kepala Sekolah [Increasing Number and Academic Quality of Students Through the Leadership Role of Principal] - Widodo Ong (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2022)
There are two main roles played by a principal of private schools. The first role is as an entrepreneur whose main task is to meet the student enrollment target as stated in Decree of Minister of National Education No. 13 of 2007. The second role is as an educational leader whose main task is to increase the student academic performance as stated in the Law No. 20 of 2003 on The National Education System. The problems encountered in the last five years have been a decrease of student enrollment and a decrease of academic performance of its students in the last three years. The goal of the study was to better understand as to how much the school principal has done to cope with the two problems. This study made use of qualitative descriptive methodology with a case study design. The subject of this research is the principal. The respondents are three teachers for interview and eleven teachers for questionnaire. The technical data collection is by interview, questionnaire and document study. The analysis of the data of the questionnaire used a Likert’s scale to assess the attitude, opinion and perception toward the principal combined with the results of the interview and document study. The results of the data analyzing show that (1) the role of the principal’s leadership in increasing the growth of the number of the students, (2) the role of the principal’s leadership in increasing the academic quality of the students, and (3) the role of the principal’s sense of entrepreneurship in increasing the number of the students have happened. These types of the principal’s roles can be considred as the alternative ways to increase the growth of the number of the students and to increase the academic quality of the students in this tight competitive era among the middle upper segmented private schools.